The Effect Of Load Carriage While Wearing Highheeled Shoes On Ankle Joint During Level And Uphill Walking - Tan, Ying (2020)
A within-subject comparative study of back pack load carriage while walking in different shoe and slope condition was performed to determine and identify the biomechanics effects on ankle joint while wearing high-heeled shoes during level and uphill walking with the effect of load carriage. Kinetic and kinematic data of 15 subjects walked in barefoot and high-heeled shoes with the selection of their preferable walking speed has been collected. Inverse dynamic method had been applied to calculate the ankle joint force and Achilles tendon force. All of the data collected had been normalized to minimize the bias of subject and statistical t-test had been performed to compare the difference between each variables. Result revealed that heel height significantly affects the ankle kinetic, where greater VGRF and ankle joint force were produced, and lower Achilles tendon force was produced as the heel height increases. Next, backpack load carriage also significantly affects the ankle kinetic, as greater VGRF and ankle joint force were experienced by the subjects and lower Achilles tendon force was found when the weight of load increases. On the other hand, the increment of slope level significantly affects the ankle kinetic, where greater VGRF and Achilles tendon force were experienced in level condition with lesser ankle joint force. Cadence, stride length and step length were reduced as the heel height, loaded backpack carriage and inclined slope increases.